An assessment of knowledge, attitude, and practice of the Kuantan community on the effects of monosaccharides on cancer - Mazlan, Muhammad Alif; Che Hasan, Muhammad Kamil; Mat Yusof, Afzan; Md Isa, Muhammad Lokman (UI Scholars Hub, 2020)
Background: Cancer knowledge, attitude, and practice (KAP) levels of communities are essential to be assessed to enhance cancer educational programs. This study aimed to determine the KAP level of the Kuantan community on the effects of monosaccharides on cancer. The association between the sociodemographic data and KAP level of the community has also been evaluated. Methods: A cross-sectional survey was performed among residents living in the Kuantan community. Only 303 of 380 responses were included in the data analysis using the chi-square test. Results: The knowledge and practice levels were moderate, whereas the attitude was at a positive level. Moreover, the association of sociodemographic factors (sex and education level) showed significant difference with the knowledge level (p ≤ 0.05). Additionally, only the age factor showed significant difference toward the practice level of the Kuantan community, with p < 0.05. Conclusion: In conclusion, although the attitude score is positive, educational programs still need to be conducted as the knowledge and practice levels of the community have moderate scores.